Políticas e práticas na escola primária catarinense (1911-1945): pedagogia tradicional ou escolanovista? - Ana Paula da Silva Freire; Ademir Valdir dos Santos (EccoS – Revista Científica)
We aimed to characterize and discuss the dispute between traditional pedagogy and the propositions of the New School in institutions of primary education in Santa Catarina during the period 1911-1945. The study is based on documents that reveal characteristics of the didactic-pedagogical school activity: books, school exercise book, terms of school inspection and educational legislation. The results indicate that in this context, continuity and change characterize the primary school of Santa Catarina, which is verified through the identification of both policies and practices that point to the coexistence between traditional pedagogy and the New School.